One-year costs of bilateral or single internal mammary grafts in the Arterial Revascularisation Trial - Gray, A; Murphy, J; Altman, D; Benedetto, U; Campbell, H; Flather, M; Gerry, S; Lees, B; Taggart, D; ART Investigators (BMJ Publishing Group, 2017)
Objective: Coronary artery bypass grafting (CABG) using bilateral internal mammary arteries (BIMA) may improve survival over CABG using single internal mammary arteries (SIMA), but may be surgically more complex (and therefore costly) and associated with impaired sternal wound healing. We report, for the first time, a detailed comparison of healthcare resource use and costs over 12 months, as part of the Arterial Revascularisation (ART) Trial. Methods: 3102 patients in 28 hospitals in seven countries were randomised to CABG surgery using BIMA (n=1548) or SIMA (n=1554). Detailed resource use data were collected covering surgery, the initial hospital episode, and for 12 months post randomisation. Using UK unit costs, total costs were calculated and compared between trial arms and for subgroups. Results: Patients randomised to BIMA spent 20 min longer in theatre (95% CI 15 to 25, p<0.001) and also required more treatment for sternal wound problems. Mean (SD) total costs per patient at 12 months were £13 839 (£10 534) for BIMA and £12 717 (£9719) for SIMA (mean cost difference £1122, 95% CI £407 to £1838, p=0.002). No tests for interaction between subgroups and treatment allocation were significant. Conclusions: At 12 months from randomisation, mean costs were approximately 9% higher in BIMA than SIMA patients, primarily due to longer time in theatre and in-hospital stay, and slightly higher costs related to sternal wound problems during follow-up. Follow-up to the primary trial endpoint of 10 years will reveal whether longer-term differences emerge in graft patency or in overall survival.